2015
DOI: 10.1016/j.chemgeo.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of porosity and permeability evolution of Mount Simon sandstone under geological carbon sequestration conditions

Abstract: A numerical model was developed with the use of reactive transport code CrunchFlow to estimate porosity, permeability and mineral composition changes of Mount Simon sandstone under typical geological carbon sequestration conditions (P=23.8 MPa and T=85 o C). The model predicted a permeability decrease from 1.60 mD to 1.02 mD for the Mount Simon sandstone sample in a static batch reactor after 180 days of exposure to CO 2-saturated brine, which is consistent with measured permeability results. Model-predicted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 44 publications
(58 reference statements)
3
62
0
Order By: Relevance
“…The secondary minerals that were finally used in the calculations are given in Table 4 and are in agreement with the ones supposed for the mass balance calculation. The kinetics data presented in Table 4 and used in this study are in agreement with other studies performed in similar temperature and pressure conditions [27,43,[50][51][52]. Table 4.…”
Section: Mass Balance Calculation and Numerical Modellingsupporting
confidence: 80%
“…The secondary minerals that were finally used in the calculations are given in Table 4 and are in agreement with the ones supposed for the mass balance calculation. The kinetics data presented in Table 4 and used in this study are in agreement with other studies performed in similar temperature and pressure conditions [27,43,[50][51][52]. Table 4.…”
Section: Mass Balance Calculation and Numerical Modellingsupporting
confidence: 80%
“…Similarly, due to the weak water–rock interaction, the decreases in the porosity and permeability of the matrix system are around 0.01% and 0.1%, which are similar with previous work . Zhang and co‐workers developed a numerical model to investigate reactive transport and porosity and permeability changes of sandstone and carbonate rock samples. Their model and experimental results showed a decrease of 7.3% in the permeability of samples, which were merged in the CO 2 ‐saturated brine, in a static batch reactor after 180 days.…”
Section: Co2 Flooding–coupled Storage Numerical Simulationssupporting
confidence: 83%
“…Zhang et al . conducted numerical simulations to study CO 2 ‐induced porosity and permeability evolution of sandstone samples taken from another targeted CO 2 storage formation – the Mount Simon Sandstone Formation . Those sandstone samples had relatively low initial porosity (less than 8%) .…”
Section: Introductionmentioning
confidence: 99%
“…conducted numerical simulations to study CO 2 ‐induced porosity and permeability evolution of sandstone samples taken from another targeted CO 2 storage formation – the Mount Simon Sandstone Formation . Those sandstone samples had relatively low initial porosity (less than 8%) . Those studies revealed that for sandstone samples with high quartz and feldspar content, four mineral dissolution and precipitation reactions (dissolution of feldspar, dissolution of quartz, precipitation of amorphous silica, and precipitation of kaolinite) played very important roles in permeability evolution of the sandstone samples.…”
Section: Introductionmentioning
confidence: 99%